The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Caracterização e Organização Social Dos Machababos a Partir dos Discursos de Mulheres Raptadas - Feijó, João (Observatório do Meio Rural, 2021)
A intensificação do conflito militar no Norte de Cabo Delgado despertou a atenção de jornalistas, investigadores, analistas de segurança e diplomatas. O facto de os rebeldes armados não darem entrevistas a jornalistas e investigadores resulta num grande desconhecimento sobre as suas dinâmicas internas nas zonas ocupadas, pelo que o mundo dos insurgentes constitui um território repleto de mistérios. Por outro lado, o rapto de centenas de jovens mulheres gera interrogações em torno do respectivo paradeiro, originando inquietação social. O pouco conhecimento existente acerca das formas de organização interna dos insurgentes resulta de testemunhos oculares de quem privou com o grupo, nomeadamente desertores ou mulheres que estiveram em cativeiro. A partir de 23 entrevistas a mulheres vítimas de agressão ou sequestro por grupos insurgentes foi possível concluir que os membros do grupo têm origens e percursos sociogeográficos heterogéneos, sendo a maioria oriunda do litoral Norte de Cabo Delgado, com registos de indivíduos provenientes do planalto de Mueda, do litoral de Nampula, assim como um crescente número de estrangeiros, provenientes da costa oriental africana e de países árabes. Os insurgentes dispõem de diferentes bases, instaladas em aldeias abandonadas por civis ou nas matas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Characterization and Social Organization of Machababos from the Discourses of Kidnapped Women - Feijó, João (Observatório do Meio Rural, 2021)
The intensification of the military conflict in Northern Cabo Delgado has attracted the attention of journalists, investigators, security analysts and diplomats. The fact that armed rebels do not give interviews to journalists and researchers results in a great ignorance about their internal dynamics in the occupied areas, and so the world of insurgents is a territory full of mysteries. On the other hand, the abduction of hundreds of young women raises questions about their whereabouts, causing social unrest. The little knowledge of the insurgents' forms of internal organization stems from eyewitness testimonies of those who lived with the group, including defectors or women who have been in captivity.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Strengthening Women’s Inclusion in Social Accountability Initiatives - Nazneen, Sohela; Silva Olivares, Maria Fernanda (2021)
In the last 20 years, social accountability initiatives have facilitated the inclusion and participation of marginalised groups in governance processes. This Policy Briefing focuses on how and what factors prove effective in strengthening women’s voice in processes holding public service providers accountable. We argue that initiatives must: (a) build technical and other forms of capacity amongst women; (b) change formal rules on women’s inclusion; (c) apply political economy analysis to unpack power dynamics, identify actors in favour of gender equality, and build a network in support of women; and (d) make long-term funding commitments for sustainable change in gender-biased norms.
Accepted: 2021-02-18T10:37:09Z Publisher: Institute of Development Studies
Keywords: *tagged; L - english / inglês; accountability / responsabilização; gender / género; social inclusion & exclusion / inclusão e exclusão social

Shaping Social Change with Music in Maputo, Mozambique - Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Manhiça, Anésio (IDS, 2021)
In Mozambique, development programmes have traditionally drawn on music as a means to promote social transformation by educating citizens on key social development issues. Shifting the focus from music as a teaching medium to music as a rich source of information can provide vital insights into public opinion and political ideas, and significantly impact the development of citizen engagement projects. Maximum gains for development and civil society agencies can be achieved by mainstreaming gender into mutual learning activities between singers, audiences, and academics.
Keywords: *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento; gender / género

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Relatório de Pesquisa Desigualdades e Resistência em Tempos de Pandemia: Impactos Da COVID-19 Nas Mulheres do Mercado Informal - Osório, Conceição; Loforte, Ana Maria; Vilanculo, Sérgio (WLSA Moçambique, 2021)
Este relatório de pesquisa buscou especificamente identificar no contexto mundial, regional e nacional as estratégias e as políticas públicas relativamente à situação das raparigas e mulheres, analisar as narrativas e discursos das organizações da sociedade civil e instituições de pesquisa, tanto as que têm como foco os direitos humanos, como as que definem como objecto a promoção da igualdade de género, e analisar o conteúdo dos media nacionais sobre a Covid-19, com destaque para as representações sobre violência de género. Para a realização da pesquisa foi importante a definição do grupo alvo, as mulheres que trabalham no informal, por serem das mais afectadas pela situação criada pela Covid-19, sendo muito pouco conhecidas as suas vozes, os seus problemas, necessidades e expectativas. A pesquisa foi enquadrada no Projecto “Mulheres e direitos humanos no contexto da COVID-19 em Moçambique” e surgiu no âmbito de uma parceria entre a WLSA Moçambique com as Aliadas e o CESC, procurando conhecer melhor como é que, em situação de pandemia, se configuravam os direitos humanos das mulheres, considerando as desigualdades estruturais e as relações desiguais de poder.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; informality / informalidade

Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude